Benefits and challenges of digital audit implementation in the Malaysian public sector: evidence from the Accountant General’s Department of Malaysia - Mokhtar, Norsyahida; Ismail, Suhaiza; Ahmad @ Abdul Mutalib, Hawa (Institut Perakaunan Negara, 2024)
Purpose: The current study aims to investigate the important benefits or advantages of digital audit implementation perceived by the internal auditors of the Accountant General’s Department of Malaysia (AGD), and examine the significant challenges faced by the AGD auditors in implementing digital audit.